Human –Social concept influenced by style and meaning in three Selected Poems of Angel Gonzalez Muniz - Mohammed, Hanan Younus (Al-Adab Journal, 2019)
Literary criticism theories stay a special framework to adopt means and methods for analyzing and dissociating literary texts. These theories always assert the linguistic structure in literary innovation and its effects on intellectual messages derived from signs resulted from uses of syntax, morphology and others. Hence, philosophical and literary vision is exposed to linguistic effects and structural uses in the structures of all literary texts. Therefore, the present study sheds light on determining Ángel González's uses of lexical items and employing different types of linguistic resources in building intellectual form of literary text in the three selected poetic texts, the common features among them, and the way of directing them to add human and social feature to his poetic production in order to express social situation in which the poet himself lives, by using similarity of lexical items and twinning them with other items to formulate a rich text with direct sense and comprehendible intellectual messages. Besides, the paper affirms the way of using verbs and their tenses, as they have an obvious effect on the concept of literary text within a framework of theoretical analysis and intellectual structure derived from the poet's mentality and reflected in the literary structure received by the reader in all temporal and circumstantial elements which Ángel González wanted to exploit for human vision, by fusing the lexical item used and its sense within text's linguistic structure and the effects of the outcomes on comprehending and realizing intellectual considerations throughout a poem or poems, and particularly those selected ones. Moreover, the study confirms that the human tendency in its social framework is the main goad which affects Ángel González's poetic talent throughout his uses of linguistic styles and means through elements and conceptions which are clearly reflected in all his creative products, especially the three selected poems.